Protection of Property Rights and Growth as Political Equilibria - Andrea Asoni (Research Institute of Industrial Economics (IFN), 2008)
This paper presents a survey of the literature on property rights and economic growth. It discusses different theoretical mechanisms that relate property rights to economic development. Lack of protection of property rights can result in slow economic growth through different channels: expropriation of private wealth, corruption of civil servants, excessive taxation and barriers to adoption of new technologies. The origins of property rights are also considered. Different theories are illustrated but more attention is paid to the social conflict view and its strengths and limitations. The second part of the paper illustrates relevant empirical works on property rights and growth.
Keywords: O11; O12; O43; P14; P16; 330; Institutions; Economic Development; Property Rights; Social Conflict View; Immaterialgüterrechte; Eigentumsrecht; Wirtschaftswachstum